PENELITIAN PENANGANAN ANAK JALANAN MELALUI RUMAH SINGGAH - Suradi Suradi (Sosio Informa, 2003)
Studies on the Coping of Street Children through Home Shelter.One among model which developed by the Ministry of Social Affairs in serving street children is "Rumah Singgah". The model was innitiated by the Ministry in 1999. The Rumah Singgah is fully conducted by community and the Ministry supports the community through fund and guidence. The study evaluates three aspects, which are organization, activities and street childreb characteristics. Those three aspects asre seen in a system. However, even though theRumah Singgah supported by enough facilities, fund and human resources but it is not optimalin terms of social servicesKata Kunci: Street Children, Home Shelter, Rumah Singgah